{FeNO}7‐Type Halogenido Nitrosyl Ferrates: Syntheses, Bonding, and Photoinduced Linkage Isomerism. Issue 5 (20th December 2018) - In‐Iam, Areenan; Wolf, Markus; Wilfer, Claudia; Schaniel, Dominik; Woike, Theo; Klüfers, Peter
Abstract: Mononitrosyl–iron compounds (MNICs) of the Enemark–Feltham FeNO 7 type can be divided into a doublet ( S =1/2) and a quartet ( S =3/2) spin variant. The latter relies on weak‐field co‐ligands such as amine carboxylates. Aqua‐only co‐ligation appears to exist in the long‐known "brown‐ring" [Fe(H2 O)5 (NO)] 2+ cation, which was prepared originally from ferrous salts and NO in sulfuric acid. A chloride variant of this species, the green [FeCl3 (NO)] − ion, was first prepared analoguosly by using hydrochloric instead of sulfuric acid. As a tetrahedral species, it is the simple prototype of sulfur‐bonded FeNO 7 ( S =3/2) MNICs of biological significance. Although it has been investigated for more than a century, neither clean preparative routes nor reliable structural parameters were available for the [FeCl3 (NO)] − ion and related species such as the [FeCl2 (NO)2 ] − ion, a prototypical dinitrosyliron species (a "DNIC"). In this work, both issues have been resolved. In addition, we report on a computational study on the ground‐ and excited‐state properties including an assignment of the chromophoric transitions. Photoinduced metastable isomers were characterised in a combined experimental and computational approach that resulted in the confirmation of a single photoinduced linkage isomer of the paramagnetic nitrosyl–metal coordination entity. Abstract : Rising to the challenge : The green [FeCl3 (NO)] − (see figure) and red‐brown [FeCl2 (NO)2 ] − chromophores may be considered simple prototypes of the MNIC and DNIC classes of nitrosyl complexes (mono‐ and dinitrosyl–iron compounds). Both species are old acquaintances of chemical science but the synthesis, characterization, and photophysical transformation of pure members has remained a challenge until now.